Closed Loop Simulation of Grinding - Steffens, K.; König, W. (CIRP annals, 1983)
Basic research in the field of grinding is chiefly concerned with the kinematics, the elastoplastic processes at the engaging cutting edges, the resultant cutting forces and the laws of thermal behaviour of the process. Linking of these subjects leads to a closed loop simulation. The theory of a new algorithm is described which reconstructs the physical chain of effect in a deterministic manner. The simulation is based on the wheel topography. It takes into account important factors such as temperature dependent work material properties and elastic deflection of the grinding wheel. The description of the physical processes at the engaging cutting edges uses a plane plastomechanical model. The momentary forces at the individual cutting edges are transformed into grinding forces. In the same way a stationary heat source is calculated from the heat produced at all individual cutting edges engaging in an interval of time. As the simulation is based on a numerical approach, stresses and heat fluxes in the contact zone can be described along the whole real contact length. The accuracy of the method is proved by predicting experimental results.